DNA metabarcoding elucidates fish larval diversity in multi-ecosystem Setiu Wetlands, Malaysia - Kasim, Noorhani Syahida; Mat Jaafar, Tun Nurul Aimi; Tan, Min Pau; Ghazali, Siti Zafirah; Mohd Abu Hassan Alshari, Norli Fauzani; Zainal Abidin, Danial Hariz; Mohd Yusoff, Ilham Syahadah; Mamat, Nur Syahirah; A. Rahim, Masazurah; Mohamad, Najiah; Jamaludin, Noorul Azliana; Mohd Nor, Siti Azizah (Elsevier, 2025)
Complementary larval and adult fish data allows a comprehensive ichthyological diversity assessment of an ecosystem. Identifying fish larvae only by morphology, however, is a tough challenge, even with standard conventional DNA barcoding. Thus, DNA metabarcoding was employed to analyse the richness and diversity of fish larvae in Setiu Wetlands. Fish larvae were collected during the dry season (June to August), across four sampling events. Each event involved two consecutive days of sampling at eight stations representing five distinct ecosystem types: freshwater river, peat swamp, mangrove swamp, mudflat, and estuary. Pooled larval DNA was amplified using universal COI primers and sequenced on the Illumina MiSeq platform. The meta- barcoding assay detected 76 species from 54 genera and 38 families were detected, with Ambassis vachellii, Chanda sp. (Ambassidae), Butis butis (Butidae), Epinephelus fuscoguttatus (Ephinephelidae) and Redigobius biko- lanus (Oxudercidae) among the most common species. The lower diversity compared to previous adult fish surveys (138 species) likely reflects seasonal sampling constraints (dry season only), differences in sampling effort, and methodological limitations of the metabarcoding approach. This study demonstrates that meta- barcoding of larval fish communities can reveal distinct diversity patterns across ecosystem types, identifying important nursery habitats and previously undetected species. The approach provides valuable complementary data to traditional surveys, enhancing our understanding of multi-ecosystem wetland biodiversity and informing targeted conservation strategies.